Synbiotic therapy in infantile colic resistant to conservative therapy: a clinical trial - Peymaneh Alizadeh Taheri; Shima Rostami; Kambiz Eftekhari; Sedigheh Danesh (Hygeia Press di Corridori Marinella, 2021)
Background: Infantile colic is a disturbing problem for parents. The Rome IV criteria are the last modality for the diagnosis of colic. Available medications have variable effects on the treatment of colic. However, no definite treatment has been identified yet. Aims: To our knowledge, few clinical trials have compared the efficacy of synbiotics in infantile colic, so the present study was conducted. Material and methods: This study was performed on 120 infants (51.66% boys; mean age: 42.09 ± 21.14 days; mean birth weight: 3,155 ± 420 g) with the diagnosis of infantile colic resistant to conservative therapy. The infants were randomly divided into groups A and B. A synbiotic containing B. infantis, L. reuteri, L. rhamnosus, and fructooligosaccharides (FOS) (PediLact® [Zist-Takhmir Co., Tehran, Iran] drop) was administered to group A, while group B received a synbiotic containing B. lactis and FOS (BBCare® [Zist-Takhmir Co., Tehran, Iran] drop). The primary outcome was the response rate to each synbiotic, and the secondary outcome was the complications of each synbiotic. Results: The response rate to both synbiotics was significant after 1 week of intervention (1.97 ± 0.91 [44.95%] versus 1.64 ± 0.77 [54.23%], p = 0.000). Both groups showed a significant response rate to each synbiotic after 1 month of intervention too (1.19 ± 0.84 [63.48%] versus 0.70 ± 0.48 [79.65%], p = 0.000). The response rate was significantly higher in group B compared to group A after 1 week (54.23% versus 44.95%) and after 1 month (79.65% versus 63.48%) of intervention. Neither synbiotic was associated with adverse effects. Conclusion: The present study showed that both synbiotics were effective in the treatment of infantile colic. However, the synbiotic containing B. lactis was significantly more effective than the synbiotic containing B. infantis, L. reuteri, and L. rhamnosus in infantile colic.